PENCATATAN PERJANJIAN LISENSI OPEN-SOURCE SOFTWARE SEBAGAI RESIDU DARI FORMALITAS HAK CIPTA - Ilham Tri Putra Mahpudin; Happy Yulia Anggraeni (LPPM Universitas Ekasakti Padang, 2023)
In two decades, technological developments have made the existence of intellectual works such as open-source software with economic inlays grow quite rapidly. This phenomenon is inseparable from the debate on the obligation to regist er computer program copyright license agreements as in Law Number 28 of 2014 concerning Copyright. This research revisits the obligation to record copyright license agreements required to reconstruct existing rules to present a new perspective of viewing OSS as one of the main sources in developing computer programs. The type of research is normative law. The approach uses legislation and conceptual. The results of the study concluded that although recording the license agreement is necessary as a proof base, recording is considered to add to the length of the bureaucratic process which can reduce interest in creativity, and cause confusion because copyright is not required to be registered